Florida Rainfall Data Sources and Types - Meijing Zhang; Young Gu Her; Katie Migiliaccio; Clyde Fraisse (EDIS)
This new 5-page document introduces the sources, providers, and types of rainfall data available to Florida researchers and residents to promote understanding of the rainfall data and their application in studies and daily life. Written by Meijing Zhang, Young Gu Her, Kati Migliaccio, and Clyde Fraisse, and published by the UF Department of Agricultural and Biological Engineering, January 2017.